Investigation of Flow Behavior around Corotating Blades in a Double-Spindle Lawn Mower Deck - Chon W.; Amano R. S. (International Journal of Rotating Machinery)
When the airflow patterns inside a lawn mower deck are understood, the deck can be redesigned to be efficient and have an increased cutting ability. To learn more, a combination of computational and experimental studies was performed to investigate the effects of blade and housing designs on a flow pattern inside a 1.1<mtext>m</mtext> wide corotating double-spindle lawn mower deck with side discharge. For the experimental portion of the study, air velocities inside the deck were measured using a laser Doppler velocimetry (LDV) system. A high-speed video camera was used to observe the flow pattern. Furthermore, noise levels were measured using a sound level meter. For the computational fluid dynamics (CFD) work, several arbitrary radial sections of a two-dimensional blade were selected to study flow computations. A three-dimensional, full deck model was also developed for realistic flow analysis. The computational results were then compared with the experimental results.